Circular bio-economy innovations for resilient refugee and host communities in East Africa - Adam-Bradford, A.; Mendum, R.; Njenga, M.; Woldetsadik, D.; Acanakwo, E. F.; Gebrezgabher, Solomie A. (2022)
Faced with water scarcity, food insecurity, and energy poverty, refugee and host communities in Kenya, Uganda, and Ethiopia are adopting circular bio-economy practices to build local resilience. Integrated interventions such as home gardens irrigated with greywater, composting, agroforestry, and briquette production enable households to recover water, nutrients, and biomass while reducing dependency on external aid. In Kalobeyei Settlement, greywater runoff from water points is now diverted to irrigate vegetable plots, increasing dry-season food production and allowing women to sell surplus greens like amaranth and jute mallow. Profits are often reinvested in household needs, such as schoolbooks and staple food items. In Uganda’s Rhino and Imvepi settlements, briquettes made from cooking waste and crop residues have reduced firewood demand and indoor smoke exposure. Locally built mud-brick stoves require just three firewood sticks to cook beans down from previous bundles offering major time and labor savings for women. Over 1,600 households have been trained, with women making up 85% of trainees in Kenya. Peer-to-peer learning has extended uptake beyond project targets. However, water shortages, lack of seeds, and delayed training undermined early agroforestry efforts, especially in Uganda. Despite these gaps, the model shows promise. By closing resource loops at the household level, these regenerative practices strengthen food and energy systems while empowering women and promoting social cohesion in crisis-affected landscapes.